THE LANGUAGE OF POLITICAL CAMPAIGN - Sutopo, Djoko (Language Circle: Journal of Language and Literature, 2009)
This study is aimed at finding out how meanings are realized in the election campaigns in the contemporary Indonesia and what role language takes in exercising power? The close-up linguistic analysis of three different texts has illustrated that the texts are rich in meanings: they make not just meanings about what goes on and why, but also meanings about relationship and attitudes, and meanings about distance and proximity. By relating specific linguistic choices to the construction and reflection of situational, cultural and ideological contexts, these three different texts have been shown to in fact encode meanings about such far reaching dimensions as: ways of talking to your die-hard fans, the experience of politicians, the responsibility of a statesman and expected behavior of a Ã¢â¬ÅgoodÃ¢â¬Â leader. Meanings of the political campaigns in contemporary Indonesia are explicitly realized in a subtle ways. The exercise of power is achieved through ideological workings of language. Public space serves a rhetorical means. Competing figures establish their voices by constructing counter-narratives in public space. ÃÂ  Key words: meanings, election campaign, cultural context, ideological context, public space, rhetorical means, counter narratives.